Criteria For Giving Car Loans to Consumers Using Sugeno's Fuzzy Concept - Rio Rahmat Yusran (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
PT XYZ is a company engaged in car loans. This company sells various kinds of cars with credit payment systems. To ensure that the provision of credit is not bad, there are several criteria that are made by the company in accordance with the criteria that have been set. There are 4 criteria that are used as standards that must be met for consumers so that the car purchase system on credit is accepted. The 4 criteria include the capacity to pay off credit (Capacity), the ability of the customer's capital (Capital), the guarantee owned by the customer to bear credit risk (Collateral) and the customer's financial condition (Condition). The problem in this research is that there are often bad credit consumers who do not pay installments in accordance with the specified time. The purpose of this research is to help companies provide credit to consumers so that they are right on target. The settlement of this case uses Fuzzy Logic which is suitable to be implemented into a computerized system to take a decision. The method used in this study is the Sugeno method using the And operator and taking the MAX value. The final result of this study is in the acceptable range with a value of 196.33 . To see the other criteria, just input each x value into the existing system.